2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6345887
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Bioimpedance cerebral monitoring. Preliminary results from measurements on stroke patients

Abstract: Electrical Bioimpedance Spectroscopy (EBIS) is currently used in different tissue characterization applications. In this work we aim to use EBIS to study changes in electrical properties of the cerebral tissues after an incident of hemorrhage/ischemic stroke. To do so a case-control study was conducted using six controls and three stroke cases. The preliminary results of this study show that by using Cole-based analysis on EBIS measurements and analyzing the Cole parameters R(0) and R(∞), it is possible to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Clinical results specifically confirmed that there exists a statistically significant (P < 0.05) larger potential difference in the scalp potential distribution of patients suffering acute/subacute ICH than the controls, which, unlike simulated results, can be measured relatively fast (<1 h). Although these results are in agreement with the results from other numerical and experimental studies, 32,34,35,37,45,46 unlike previous experimental studies using stroke lesions from the chronic phase, i.e., lesions over a month old, 34,35,45 we obtained EIS recordings from patients in the acute and subacute phases, i.e., lesions less than five days old, to demonstrate the potential usefulness of EBI for the prehospital triage of patients suffering acute/subacute brain injury.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Clinical results specifically confirmed that there exists a statistically significant (P < 0.05) larger potential difference in the scalp potential distribution of patients suffering acute/subacute ICH than the controls, which, unlike simulated results, can be measured relatively fast (<1 h). Although these results are in agreement with the results from other numerical and experimental studies, 32,34,35,37,45,46 unlike previous experimental studies using stroke lesions from the chronic phase, i.e., lesions over a month old, 34,35,45 we obtained EIS recordings from patients in the acute and subacute phases, i.e., lesions less than five days old, to demonstrate the potential usefulness of EBI for the prehospital triage of patients suffering acute/subacute brain injury.…”
Section: Discussionsupporting
confidence: 77%
“…Despite the limitations of the study, like the low statistical power, the obtained results agree with previous bioimpedance-related studies. 32,34,35,37,45,46 The results indicate that a hemorrhagic brain lesion generates spatial changes in voltage, which can be recorded directly on scalp, thus supporting this type of bioimpedance technology for potential early detection of brain ICH.…”
Section: Discussionmentioning
confidence: 77%
“…Consequently, a portable and inexpensive diagnostic tool to detect stroke quickly, which can be used in primary healthcare units and ambulances, is urgently needed. Because biological tissues have different impedance characteristics under normal physiological conditions and different pathological states [5,6,7,8], impedance methods are proposed to detect stroke [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. …”
Section: Introductionmentioning
confidence: 99%
“…In this method, the impedance before stroke needs to be measured to serve as a reference [16]. Second, because the impedance distribution of both brain hemispheres of normal human is symmetrical, whereas it is otherwise for a stroke patient, it is possible to detect stroke by comparing whether the impedance distribution is symmetrical for the hemispheres in a subject’s head [17,18,19,20]. This method requires that the shape of the subject’s two hemispheres should be basically symmetrical and that the electrodes must be strictly placed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Effective measurements to determine which CCH was damaged by unilateral stroke lesion were also studied [27, 28]. Thus, the damaged and undamaged CCHs can be determined in practice.…”
Section: Introductionmentioning
confidence: 99%